Validating LENT score in malignant pleural effusion - Alia Alawneh; Fadi Abu Farsakh; Mahmoud Smadi; Shaher Samrah (Future Science OA)
Aim: LENT score was developed to predict survival in malignant pleural effusion (MPE), this study aims to validate this score. Objectives: Validate LENT Prognostic Score for MPE and explore survival in these patients. Methods: Retrospective analysis of 202 patients who had MPE and received drainage between January 2013 and June 2015. Results: Median survival was 2.98 months. Patients were classified according to LENT score as low, moderate and high-risk groups: 5 (4.2%), 61 (50.8%), and 54 (45%), respectively. Kaplan–Meier curve showed median survival for each group: 9.41, 5.36 and 0.56 months, respectively, p-values <0.001. AUC for 1, 3 and 6 months: 0.741, 0.781, 0.790, respectively, p-values <0.001. Conclusion: LENT score is valid for predicting survival in patients with MPE.